Centrally administered lipopolysaccharide elicits sympathetic excitation via NAD(P)H oxidase-dependent mitogen-activated protein kinase signaling - Zhang, Zhi-Hua (2010)
OBJECTIVE: The mechanisms by which inflammation activates sympathetic drive in heart failure and hypertension remain ill-defined. In this study, an intracerebroventricular (ICV) injection of lipopolysaccharide (LPS) was used to induce the expression of cytokines and other inflammatory mediators in the brain, in the absence of other excitatory mediators, and the downstream signaling pathways leading to sympathetic activation were examined using ICV injections of blocking or inhibiting agents. METHODS AND RESULTS: In anesthetized rats, ICV injection of LPS (5 µg) increased (p<0.05) renal sympathetic nerve activity, blood pressure and heart rate. LPS increased (p<0.05) hypothalamic mRNA for NAD(P)H oxidase subunits p47 (phox) and gp91(phox), NAD(P)H-oxidase-dependent superoxide generation, hypothalamic mRNA for tumor necrosis factor (TNF)-α, cyclooxygenase-2 (COX-2), and cerebrospinal fluid (CSF) levels of TNF-α and prostaglandin E2 (PGE(2)). In the paraventricular nucleus of hypothalamus, dihydroethidium staining for superoxide expression and c-Fos activity (indicating neuronal excitation) increased. The superoxide scavenger tempol significantly (p<0.05) diminished the expression of inflammatory mediators, as well as superoxide expression and neuronal excitation in paraventricular nucleus. SB203580 (p38 mitogen-activated protein kinase inhibitor) also reduced the expression of inflammatory mediators in hypothalamus and CSF. Tempol, apocynin (NAD(P)H oxidase inhibitor), SB203580 and NS398 (COX-2 inhibitor) all reduced CSF PGE(2) and the sympatho-excitatory response to LPS. LPS also increased angiotensin II type 1 receptor mRNA, a response blocked by apocynin and tempol but not by SB203580. CONCLUSION: These findings suggest that central inflammation in pathophysiological conditions activates the sympathetic nervous system via NAD(P)H-oxidase and p38 mitogen-activated protein kinase dependent synthesis of PGE(2).